LindungiAku: Sexual Harassment Educational Media Through Pop-Up Books - Utami, Wulan Tri Puji; Trisnani, Novy; Astuti, Anita Dewi (Universitas Pendidikan Ganesha, 2022)
Elementary school students are students who are vulnerable to sexual violence and harassment, so we need media that can provide students with an understanding of the dangers of sexual violence and harassment. The purpose of this research is to develop a valid and effective pop-up book as an educational medium for violence and sexual harassment to elementary school students. This type of research is ADDIE model development research. The subjects in this study were 6 validators and 10 elementary school students. The instruments used in data collection were questionnaire sheets, interview sheets, and validation sheets. The data analysis technique used is descriptive qualitative and quantitative. The research data shows that the pop-up book meets the valid criteria, with a validity score of 4.40 from material experts, 4.70 from media experts, and 3.85 from practicing experts. The results of the hypothesis test show a significance value of 0.000 so the research hypothesis that there is an effectiveness of the Protect Aku pop up book as an educational medium for elementary school students can be accepted. So based on these results it can be concluded that the pop-up book that was developed has been valid and effective to be used as a medium for education on violence and sexual harassment to elementary school students.